FAKTOR-FAKTOR YANG MEMPENGARUHI KELANCARAN DISTRIBUSI PUPUK BERSUBSIDI PADA PETANI PADI SAWAH (Studi Kasus: Desa Purbaganda Kecamatan Pematang Bandar Kabupaten Simalungun) - Muhammad Fadly; Zulkarnain Lubis; Mitra Musika (Universitas Medan Area, 2017)
Subsidized fertilizer is one of the means of production is the availability of subsidized by the government to farmers and Retail Price (MRP) was regulated by Government Regulation. 87 / Permentan / SR.130 / 12/2011. The purpose of this study was to determine the influence of factors as price, distance, number of requirements, and policies for the smooth distribution of subsidized fertilizer distribution and to determine the constraints faced by farmers in obtaining subsidized fertilizer. The experiment was conducted in North Sumatra province Simalungun. This region is determined by purposive sampling. The consideration is that the study site is an area of crop production centers and one of the largest users of fertilizers in North Sumatra. The population in this study is that farmers receiving subsidized fertilizer in the village Purbaganda. Total population is 328 families with a total sample of 30 families. Data were analyzed using analysis of X² (Chi Square). The results showed that the factors that affect the smooth distribution of subsidized fertilizer is the price factor and the time distribution of fertilizer policy.While the distance factor and the factors determining fertilizer requirements do not affect the level of the smooth distribution of fertilizers. Constraints faced by farmers in the smooth distribution of subsidized fertilizer prices among other factors, the time distribution of fertilizer policies and lack of venture capital to the farmers as well as non optimal preparation of Definitive Plan of Group ( RDKK ) at the level of the farmer groups